Relasi Agama dan Negara, Nasionalisme dalam Perspektif Islam, dan Pancasila sebagai Landasan Pendidikan Karakter - Yuyu Wahyudin (Hikamatzu | Journal of Multidisciplinary, 2026)
Indonesia, as the country with the largest Muslim population, adopts neither a theocratic nor a secular state system, making the relationship between Islam, nationalism, and the state a significant topic of academic discussion. This study aims to examine the relationship between Islam and the Indonesian state, explore the concept of nationalism from an Islamic perspective, and analyze the role of Pancasila as the foundation of national character. The study employs a qualitative library research approach using descriptive-analytical methods by reviewing the Indonesian Constitution, Islamic teachings, scholarly literature, and relevant academic references on religion, nationalism, and Pancasila. The findings indicate that Indonesia applies a symbiotic relationship between religion and the state, in which religion provides moral and ethical guidance while the state guarantees religious freedom and social harmony. Islamic nationalism is understood as religious nationalism that promotes love for the homeland (hubbul wathan minal iman), unity, justice, and social responsibility. Furthermore, Pancasila serves as a common platform that harmonizes Islamic values with Indonesia's pluralistic identity and functions as the foundation for developing religious, democratic, humanistic, and tolerant character. The study concludes that the integration of moderate Islamic values and Pancasila is essential for strengthening national identity, promoting social cohesion, and fostering resilient character education in contemporary Indonesia.